Chemical structures and electrical properties of atomic layer deposited HfO2 thin films grown at an extremely low temperature (<= 100 degrees C) using O-3 as an oxygen source - Kim, Jeong Hwan; Park, Tae Joo; Kim, Seong Keun; Cho, Deok-Yong; Jung, Hyung-Suk; Lee, Sang Young; Hwang, Cheol Seong (ELSEVIER, 2014)
The properties of atomic layer deposited (ALD) HfO2 films grown at low temperatures (<= 100 degrees C) were examined for potential applications in flexible display and bioelectronics. A saturated ALD growth behavior was observed even at an extremely low temperature (30 degrees C) due to the strong oxidizing potential of O-3. However, HfO2 films grown at low temperatures showed a low film density and high impurity concentration, because the thermal energy during film growth was insufficient to remove ligands completely from Hf ions in precursor molecule. This resulted in low dielectric constant and high leakage current density of the films. Nevertheless, HfO2 film grown at 100 degrees C using O-3 gas with a high concentration (390 g/Nm(3)) showed a tolerable impurity concentration with the dielectric constant of 16 and breakdown field of similar to 4 MV/cm, which are approximately two-thirds of those of HfO2 film grown at 250 degrees C. C) 2013 Elsevier B.V. All rights reserved.
Keywords: OXIDANT; METAL; SI; INTERFACE; DEFECTS; ALD; XPS